Impact of health investment on household income distribution: insights from China’s longitudinal survey data - Zheng, Lili; Hou, Wenhua; Huang, Ming (Frontiers in Public Health, 2024)
This paper makes a distinctive contribution to the literature by examining the impact of health investment on household income distribution, drawing from data spanning over ten years from the China Nutrition and Health Survey. Our empirical analysis reveals robust evidence of a positive association between health investment and both absolute and relative income levels across various demographic and occupational groups. Unlike previous studies, we explore the nuanced pathways through which health investment influences income, including its effects on illness duration, employment opportunities, effective working time, and educational attainment. Employing rigorous methodological approaches such as quantile regression and cross-sectional data modeling, we provide comprehensive insights into the heterogeneous effects of health investment on income distribution. Notably, our study sheds light on the dynamic nature of this relationship, demonstrating that as income levels rise, the impact of health investment on income becomes more pronounced. Moreover, our analysis of health investment's influence on income mobility underscores its role in facilitating upward mobility, particularly for low-income households. Overall, our findings offer valuable guidance for policymakers in designing targeted interventions aimed at achieving more equitable income distribution through strategic health investment initiatives.